2017
DOI: 10.1016/j.bbr.2017.05.039
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: BNDF heterozygosity is associated with memory deficits and alterations in cortical and hippocampal EEG power

Abstract: Brain derived neurotrophic factor (BDNF) plays a pivotal role in structural plasticity, learning, and memory. Electroencephalogram (EEG) spectral power in the cortex and hippocampus has also been correlated with learning and memory. In this study, we investigated the effect of globally reduced BDNF levels on learning behavior and EEG power via BDNF heterozygous (KO) rats. We employed several behavioral tests that are thought to depend on cortical and hippocampal plasticity to varying degrees: novel object reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
(65 reference statements)
3
15
0
Order By: Relevance
“…qRT-PCR of hippocampal tissue showed that the single FLRT2 allele deletion results in a reduction of the FLRT2 mRNA levels in both in male (~47% reduction) and in female (~40% reduction) mice (Fig. 1E ), which is in agreement with the inhibition in the level of expression of specific proteins in other studied single-allele knockout mice 24 26 .
Figure 1 FLRT2+/− mice do not present with gross, detectable phenotypical abnormalities.
…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…qRT-PCR of hippocampal tissue showed that the single FLRT2 allele deletion results in a reduction of the FLRT2 mRNA levels in both in male (~47% reduction) and in female (~40% reduction) mice (Fig. 1E ), which is in agreement with the inhibition in the level of expression of specific proteins in other studied single-allele knockout mice 24 26 .
Figure 1 FLRT2+/− mice do not present with gross, detectable phenotypical abnormalities.
…”
Section: Resultssupporting
confidence: 85%
“…Conventional full knockouts animals were not used in the present study as previous reports demonstrated that the vast majority of homozygous FLRT2 knockout animals die at embryonic day 12–15 18 , 22 and therefore cannot be used to study the importance of FLRT2 in postnatal brain functions. The use of heterozygous knockout animals constitute a widely accepted tool for the identification of molecular components implicated in the regulation of synaptic plasticity and higher order cognitive functions 24 26 . Our observations of the effects of the genetic suppression of FLRT2 via haplodeficiency in female and male mice propose FLRT2 as a critical molecular component regulating adult synaptic plasticity and suggest a sex-dependent implication of FLRT2 in the promotion of hippocampus-dependent memory functions.…”
Section: Introductionmentioning
confidence: 99%
“…For spectral power analysis, amplified and filtered cortical EEG data were digitized at a sampling frequency of 200 Hz, as described previously [ 31 , 63 ]. The digitized data were then subjected to a fast Fourier transformation from 0.5 to 100 Hz with an interval of 0.2 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study confirmed that HBO preconditioning promoted neovascularization via increasing the expression levels of SDF-1 and CXCR4 in transplanted skin flaps of rats [9] . Brain-derived neurotrophic factor (BDNF) has a pivotal role in structural plasticity, learning, and memory [10] . It prevents neurodegeneration and acts as one of the synaptic plasticity markers.…”
Section: Introductionmentioning
confidence: 99%